Theosebia: A Presbyter of the Catholic Church - Ramelli, Ilaria (Journal of feminist studies in religion, 2010)
Theosebia was Gregory of Nyssa's sister and a presbyter. She probably substituted for her brother during his exile and supported him against "Arianism," as Ramelli's scrutiny of the sources and comparison with contemporary women's ministries in Cappadocia demonstrate. Ramelli's conclusion constitutes an advancement in research with remarkable theoretical implications, both because women presbyters are scarcely attested in the "orthodox" church and in the light of Gregory of Nyssa's and Origen's theology of ministry and the existence of women presbyters in their epochs. Gregory's evaluation of women's ministry—and exegesis of New Testament passages on women—was inspired by Origen, who deemed it grounded in apostolica auctoritas, admitted women's ministeria including presbyterate, and overcame difficult New Testament passages through allegory. While Gregory Nazianzen valued Theosebia's ordination, Gregory of Nyssa ascribed priesthood to Macrina, for a conception of ministry inherited from Origen. A parallel emerges between Gregory of Nyssa's opposition to slavery and his ideas on women, and his praxis in both respects. Origen's orientation to the telos influenced him: the telos, without discrimination of women or slaves, is normative for this life. Theological perspectives informed social realities.